If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + y + 2x + 2 = 39 Reorder the terms: 2 + x + 2x + y = 39 Combine like terms: x + 2x = 3x 2 + 3x + y = 39 Solving 2 + 3x + y = 39 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + 3x + -2 + y = 39 + -2 Reorder the terms: 2 + -2 + 3x + y = 39 + -2 Combine like terms: 2 + -2 = 0 0 + 3x + y = 39 + -2 3x + y = 39 + -2 Combine like terms: 39 + -2 = 37 3x + y = 37 Add '-1y' to each side of the equation. 3x + y + -1y = 37 + -1y Combine like terms: y + -1y = 0 3x + 0 = 37 + -1y 3x = 37 + -1y Divide each side by '3'. x = 12.33333333 + -0.3333333333y Simplifying x = 12.33333333 + -0.3333333333y
| -4(-6x+3)=-3x | | 5x+5x+3=32 | | 11x+7=15x-5 | | 6x^3+3x^3=18x | | x+3*4=9 | | 20x+11=360 | | -138-4x=192+11x | | x(x+3)=35 | | -2.67x-8.4=6.072+0.03x | | y=(-0.25)x+50 | | -230+2x=19+3x | | (t+z)=45z+67 | | g(X)=x-3+2 | | 2d-4=-3 | | 6x-15+4x+8=3x+9+7x-16 | | 3x+20=1500 | | 2g+7=15 | | -11+2x=19+3x | | 24x+11=123 | | -20+13x=22+11x | | 3c+2p=78 | | X-9=-3+8 | | 2b+1=-9 | | 2*-1.6+6y=-12 | | -3(7m+4)=20-5m | | 2p-4=3 | | 3x=(x-56) | | 3x+10x=5x+4x | | 7(6+3x)=105A | | 5y-3=-15 | | 25x+0.6=-30 | | 2q^2-12q=0 |